2021
DOI: 10.3390/sym13091607
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Fine Particle Ultrasonic Coagulation

Abstract: This paper describes the studies conducted in order to identify the limits of ultrasonic exposure’s effect on the fine particle coagulation process. It has been established as a result of the studies that ultrasonic exposure with a sound pressure level of 160 dB is capable of ensuring coagulation of particles sized 2.5 µm with efficiency δ = 83%. An increase of the coagulation up to 13% is induced with generation of swirling flows. The suggested approach to increasing the coagulation efficiency owing to vortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
3
0
4
Order By: Relevance
“…19,20) Gallego-Juarez et al constructed an experimental apparatus (about 5 m 3 in volume) using an ultrasonic source consisting of a stepped vibrating plate that produced transverse vibrations and showed that the mass concentration of fine particles was reduced to one-tenth in 15 min at a power of 400 W. [21][22][23] Khmelev et al showed that an ultrasonic system with a piston radiator agglomerated 83% of PM 2.5 particles at a sound pressure level of 160 dB. 24,25) They also showed that a combination of inertial dust collection and an ultrasonic vibration system with a volume of about 0.06 m 3 agglomerated 85% of PM 2.5 particles. 26) Houda et al conducted agglomeration experiments using a cylindrical vibrating plate ultrasonic source 27) with constant input power and obtained an 86% agglomeration efficiency at a total input power of 20 W. 28) The volume of the agglomeration section of this device was about 1500-2500 cm 3 .…”
Section: Introductionmentioning
confidence: 99%
“…19,20) Gallego-Juarez et al constructed an experimental apparatus (about 5 m 3 in volume) using an ultrasonic source consisting of a stepped vibrating plate that produced transverse vibrations and showed that the mass concentration of fine particles was reduced to one-tenth in 15 min at a power of 400 W. [21][22][23] Khmelev et al showed that an ultrasonic system with a piston radiator agglomerated 83% of PM 2.5 particles at a sound pressure level of 160 dB. 24,25) They also showed that a combination of inertial dust collection and an ultrasonic vibration system with a volume of about 0.06 m 3 agglomerated 85% of PM 2.5 particles. 26) Houda et al conducted agglomeration experiments using a cylindrical vibrating plate ultrasonic source 27) with constant input power and obtained an 86% agglomeration efficiency at a total input power of 20 W. 28) The volume of the agglomeration section of this device was about 1500-2500 cm 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation is accelerated in turbulent flows [48], under the action of acoustic waves [49,50], under the combined action of ultrasound and vortex motion. Such a combined effect is successfully studied in the works of Khmelev et al [51][52][53].…”
Section: Aerosol Particle Coagulationmentioning
confidence: 99%
“…формирование стоячей волны, вследствие чего в существенно возрастает уровень звукового давления. Таким образом, в пространстве между излучателем и отражателем может быть реализован процесс коагуляции высокодисперсных частиц [10].…”
Section: таблица 1 -технические характеристики ультразвуковых излучат...unclassified
“…Решениям указанной проблемы может служить создание нового типа излучателей представляющие собой изгибноколеблющиеся диски [8]. Колебания таких излучателей на заданной моде на частотах более 22 кГц с уровнями давления до 170 дБ формируются последовательно установленными и пьезоэлектрическими преобразовате-лями [4,10]. Дисковые излучатели могут иметь размеры излучающих поверхностей более 1 м 2 и способны осуществлять вывод в воздух до 60% от энергии, затрачиваемой на формирование ультразвуковых колебаний.…”
Section: Introductionunclassified